2019
DOI: 10.31871/ijntr.5.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of NACA 0012 Airfoil in Air-Sand Particle Two-Phase Flow at Reynolds Number of Re=1.76×106

Abstract: The current study deals with numerical simulations of a National Advisory Committee of Aeronautics (NACA) airfoil, NACA 0012, using a commercial Computational Fluid Dynamics (CFD) Code, in air phase flow as well as in two-phase flow of air and sand particles, which consisted of 1 percent and 5 percent sand particles in air. The simulations where accomplished for Reynolds number of Re=1.76×10 6 , at various angles of attack, on Realizable k-ε turbulence model and the injection of the particles was succeeded usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The NACA 63-215 airfoil demonstrated the least sensitivity to dust accumulation, exhibiting excellent performance across different AOAs and only experiencing a minor decrease in aerodynamic characteristics compared to other airfoils. Douvi et al numerically investigated the aerodynamic characteristics of the S809 [146,147] and NACA 0012 [148,149] airfoils within a Reynolds number range of 1 × 10 6 to 3 × 10 6 while considering different concentrations of sand particles in the airflow. The findings revealed that irrespective of the airfoil type and Re, an increase in AOA and sand particle concentration leads to elevated degradation of performance.…”
Section: Dust and Sandmentioning
confidence: 99%
“…The NACA 63-215 airfoil demonstrated the least sensitivity to dust accumulation, exhibiting excellent performance across different AOAs and only experiencing a minor decrease in aerodynamic characteristics compared to other airfoils. Douvi et al numerically investigated the aerodynamic characteristics of the S809 [146,147] and NACA 0012 [148,149] airfoils within a Reynolds number range of 1 × 10 6 to 3 × 10 6 while considering different concentrations of sand particles in the airflow. The findings revealed that irrespective of the airfoil type and Re, an increase in AOA and sand particle concentration leads to elevated degradation of performance.…”
Section: Dust and Sandmentioning
confidence: 99%
“…The NACA 63-215 airfoil demonstrated the least sensitivity to dust accumulation, exhibiting excellent performance across different angles of attack and only experiencing a minor decrease in aerodynamic performance compared to other airfoils. Douvi et al investigated numerically the aerodynamic characteristics of S809 [147,148] and NACA 0012 [149,150] airfoils within a Reynolds number range of 1×10 6 to 3×10 6 , while considering different concentrations of sand particles in the airflow. The findings revealed that irrespective of the airfoil type and Reynolds number, an increase in angle of attack and sand particle concentration leads to elevated degradation of performance.…”
Section: Dust and Sandmentioning
confidence: 99%
“…However, the majority of research is focused on the study of air-water two-phase flow, while there is less study volume and corresponding results and data of air-solid two-phase flow. Douvi et al [1] studied the effects of air-sand flow over NACA 0012 airfoil at Reynolds (Re) 1.76 × 10 6 and detected a degradation in lift coefficient and an increase in drag coefficient due to the presence of the second phase, for a wide range of angles of attack. At the same time, the solid particles appear to concentrate, for lower angles of attack, mainly at the upper surface and in the region between the leading edge and the middle of lower surface.…”
Section: Introductionmentioning
confidence: 99%